Grazing intensity on the lipid profile in bovine milk in the Colombian dry tropic - Mojica-Rodríguez, Edwin; Castro-Rincón, Edwin; Carulla-Fornaguera, Juan Evangelista; Lascano-Aguilar, Carlos Eduardo (Agronomía Mesoamericana, 2019)
Introduction. It has been suggested that the lipid profile in bovine milk affects human health, and it has been identified that conjugated linoleic acid (C9 t11 ALC) could have anticarcinogenic effects.In the high tropics the effect of feeding on lipid profile of milk has been investigated, but few studies have been done in the low tropics. Objective. The objective was to evaluate the effect of three grazing intensities (1, 2 and 3 animals ha-1) in Guinea cv Tanzania (Megathyrsus maximus) on the production, composition and lipid profile in the milk of cross breed cows in different thirds of lactation. Materials and methods. From september to october 2013, two groups of nine animals (three cows in each third of lactation) were selected, and one cow per third of lactation was assigned to each grazing intensity (treatment), during 42 days of evaluation in a replicated 3 x 3 Latin Square design. Results. Milk production did not differ (p>0.05) among treatments and was higher (p<0.05) in cows in early lactation. The treatments did not affect (p>0.05) the composition of the milk, but solids and fat concentration tended (p<0.10) to increase with third of lactation. Bovine milk fat in pasture managed with grazing intensity of 2.0 and 3.0 animals ha-1 had a higher (p<0.05) concentration of CLA (c9 t11) and of polyunsaturated fatty acids (PUFA) than when the grass was managed with 1.0 animal ha-1. The third of lactation did not influence (p>0.05) the concentration of CLA (c9 t11) and PUFA. Conclusion. Management of the cv Tanzania with grazing intensities of 2.0 and 3.0 animals ha-1 resulted in the highest levels of CLA (c9 t11) and PUFA in milk fat, which could have positive effects on human health.